Estrategias didácticas selectas para el fortalecimiento de la expresión escrita: un reto para docente y estudiantes del quinto grado de Educación General Básica - Pardo Merino, Diego Andrés (2025)
The study titled “Selected Didactic Strategies for Strengthening Written Expression: A Challenge for Teachers and Fifth-Grade Students in General Basic Education” aims to determine the impact of didactic strategies on enhancing written expression in the fifth grade at Enrique Aguirre Bustamante Basic Education School during the 2024-2025 academic period. The research is guided by the following specific objectives: to diagnose the level of written expression in fifth-grade students, to select specific didactic strategies to improve their written expression, and to design an alternative framework to foster the development of written expression. The research methodology incorporated scientific, analytical, synthetic, statistical, and descriptive methods. Adopting a mixed-methods approach, the study is descriptive in nature and follows a quasi-experimental design. Data were collected through a teacher interview and a diagnostic evaluation administered to the students. The study sample consisted of one teacher and 15 students. The diagnostic evaluation revealed the students’ levels of written expression, showing that a significant percentage had borderline writing skills, a considerable percentage exhibited moderate deficiencies in writing, and a similar percentage demonstrated normal writing abilities. These findings highlight the need for targeted improvement measures. Consequently, specific didactic strategies were selected to strengthen written expression, culminating in the development of the alternative framework “Selected Didactic Strategies: The Magic of Writing Well”, aimed at fostering written expression